Industrialisierungsprobleme in Jamaika - Haas, Hans-Dieter (ERDKUNDE, 1974)
Many developing countries regard increased efforts at industrialisation as the only proper way of achieving a rate of economic development which is healthy and equips them for the future. In many of these countries, however, the hoped-for successes have not taken place. One example is Jamaica where, in recent years, state efforts have led to the widespread establishment of industry in the Kingston-Spanish Town urban agglomeration. In spite of new job opportunities, the growing influx of rural dwellers into the urban peripheral areas has resulted in a rising rate of unemployment. This is particularly marked among the lower age groups (e.g. the 14-24 age group has a 32% unemployment rate). In addition, the legislation for industrial expansion has in large measure attracted foreign export industries to the country which neither process locally available raw materials not manufacture goods for the domestic market. Because of this, the between-plant linkages which are so vital to the process of industrialisation do not develop. In spite of the low wages earned both by unskilled and by newly trained workers, production costs in Jamaica are relatively high (frequent power failures, high transport costs, small domestic market) and this has a negative in fluence on entrepreneurial decisions in relation to further industrial establishement. Jamaican industrial planned is geared to targets for the year 1990 but it is only since 1972 that a more pronounced emphasis on the utilisation of existing local resources has emerged, especially through greater encouragement of agriculture. The products of an efficient agricultural industry, it is hoped, could be sold on the enlarged market of the CARIFTA Free Trade Area which was set up in 1968.